CENTRAL ASIAN WAQF STUDIES DURING COLONIAL, SOVIET, AND INDEPENDENCE PERIODS: A LITERATURE REVIEW - Uktambek, Sultonov; Avazbek, Ganiyev; Bakar, Osman (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2023)
This article is aimed at providing a literature review of waqf studies in Central Asia during the last 150 years since the 1860s and the 1870s until the present. One of the distinctive features of the economic development of the Islamic world is the institution of waqf, which is an integral part of the social history of Muslim society as well as one of its values. This feature is especially true of Central Asia now comprising the five independent republics of Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan, and Turkmenistan, which used in the past to be flourishing centres of Islamic civilisation, and which are in possession of a rich waqf legacy. The bibliographical survey of waqf literature in Central Asia spans the whole 150-year period which is divided into three phases, namely the Czarist colonial period (1870s-1917), the Soviet period (1920s-1930s till 1992), and the independence period (1992 until the present). Special attention is paid to the historiography of waqf institution in the region, especially pertaining to waqf foundations, and the extensive waqf literature that was generated over the centuries by the institution. The article concludes with a summary of the significance of the study for contemporary waqf studies, particularly in Uzbekistan.